Death from the heavens a history of strategic bombing - Werrell, Kenneth P. (Naval Institute Press, 2009)
Death from the Heavens is a survey of strategic bombardment from its beginnings to date. It covers the theory, hardware, and operations of this specialized type of warfare. It is based on both primary and secondary sources and is aimed at the general reader who has an interest in aviation or military history. While by necessity primarily focused on American activities, it puts these into a larger context and does include activities of foreign countries, primarily the British, Germans, and Russians. And while the book is dominated by aircraft, it does cover both air-to-surface and surface-to-surface missiles. It covers the topic in terms of chronology, nationality, actual operations, and technology.Finally, this is more than a narrative, containing both analysis and criticisms and concludes by calling into question the value of strategic bombardmen